2017
DOI: 10.1002/rnc.3890
|View full text |Cite
|
Sign up to set email alerts
|

Fast terminal sliding‐mode finite‐time tracking control with differential evolution optimization algorithm using integral chain differentiator in uncertain nonlinear systems

Abstract: SummaryThis paper presents a fast terminal sliding-mode tracking control for a class of uncertain nonlinear systems with unknown parameters and system states combined with time-varying disturbances. Fast terminal sliding-mode finite-time tracking systems based on differential evolution algorithms incorporate an integral chain differentiator (ICD) to feedback systems for the estimation of the unknown system states. The differential evolution optimization algorithm using ICD is also applied to a tracking control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…To effectively settle this issue, a novel STA with TDE was proposed for robot manipulators recently . Exciting results were reported with this method, but improvement can still be made for better performance in the following two aspects: (1) the robust term used in the work of Kali et al, was traditional SM control with linear error dynamics, which may result in slow convergence and low control accuracy around the equilibrium point, and it has been demonstrated that terminal SM (TSM) control can ensure better control performance than the traditional SM one; and (2) the standard STA was used and may lead to relative poor performance under the situation that system states are far from the equilibrium point.…”
Section: Introductionmentioning
confidence: 99%
“…To effectively settle this issue, a novel STA with TDE was proposed for robot manipulators recently . Exciting results were reported with this method, but improvement can still be made for better performance in the following two aspects: (1) the robust term used in the work of Kali et al, was traditional SM control with linear error dynamics, which may result in slow convergence and low control accuracy around the equilibrium point, and it has been demonstrated that terminal SM (TSM) control can ensure better control performance than the traditional SM one; and (2) the standard STA was used and may lead to relative poor performance under the situation that system states are far from the equilibrium point.…”
Section: Introductionmentioning
confidence: 99%
“…Extracting the derivatives of real-time signals is a common problem. For the signals that are encountered in practical applications, developing the differentiator to take derivative is a realistic option [25]. The general structure of the differentiator is expressed as:…”
Section: Nonlinear Integration Chain Tracking-differentiatormentioning
confidence: 99%
“…[15][16][17][18][19][20] Originally, linear error dynamics were combined with TDE leading to asymptotic stability, which, however, is not robust enough for some complex systems under strong lumped disturbance. Thus, the terminal sliding mode (TSM) control and its improved version, [21][22][23][24][25][26][27] which can ensure finite-time stability and high tracking precision, were integrated with TDE. [28][29][30] These TDE-based TSM controllers can effectively take advantage of TDE and TSM techniques, resulting in model-free robust controllers while still conquering the practical limitations of their own.…”
Section: Introductionmentioning
confidence: 99%